2009
DOI: 10.1029/2009gl040434
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental and higher‐mode Rayleigh wave characteristics of ambient seismic noise in New Zealand

Abstract: In order to use ambient seismic noise for mapping Earth's structure, it is important to understand the spatio‐temporal characteristics of the noise field. This study uses data collected during four austral winter months of 2002 to investigate New Zealand's ambient seismic noise field in the double‐ocean‐wave‐frequency range (0.1–0.3 Hz). It is shown via beamforming analysis that there are two distinct dispersive waves in the data. These waves can be separated. Their estimated phase velocities (2.5–2 and 4–3 km… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 20 publications
(30 reference statements)
4
54
0
Order By: Relevance
“…Most of the literature on the SM noise sources focuses on the Pacific and Atlantic oceans (e.g. Haubrich & McCamy 1969;Friedrich et al 1998;Chevrot et al 2007;Gerstoft & Tanimoto 2007;Brooks et al 2009;Koper et al 2010;Behr et al 2013) or on the global scale (Aster et al 2008;Gerstoft et al 2008;Stutzmann et al 2012) and very few on the Indian (e.g. Koper & De Foy 2008;Sheen 2014) and the Southern oceans (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the literature on the SM noise sources focuses on the Pacific and Atlantic oceans (e.g. Haubrich & McCamy 1969;Friedrich et al 1998;Chevrot et al 2007;Gerstoft & Tanimoto 2007;Brooks et al 2009;Koper et al 2010;Behr et al 2013) or on the global scale (Aster et al 2008;Gerstoft et al 2008;Stutzmann et al 2012) and very few on the Indian (e.g. Koper & De Foy 2008;Sheen 2014) and the Southern oceans (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the scattering usually present in the surface waves, together with the strong directionality of the noise wavefield, can make challenging the recognition of the arrivals (Pedersen et al 2007;Lepore et al 2016). Similar to Brooks et al (2009), the fundamental SWD mode and at least two higher order modes were identified in both the frequency bands.…”
Section: Modal Analysis Of the Dispersion Curvesmentioning
confidence: 57%
“…If the distribution of the noise sources is limited in space and the noise wavefield is strongly directional, some difficulties are encountered in retrieving the GF and extracting SWD curves at frequencies lower than 1 Hz especially for distant sources (Halliday and Curtis 2008). In such a case, the identification of the modes is challenging (Shapiro et al 2001;Gouédard et al 2008;Brooks et al 2009;Yao et al 2011;Kimman et al 2012;Rivet et al 2015;Ma et al 2016): even though the fundamental and first modes are often recognised, higher modes are observed only for some datasets. The recognition of the fundamental mode is straightforward, since its scattering is predominantly in the forward direction and the overlapping with the higher modes is weak (e.g., Bensen et al 2008).…”
Section: Modal Analysis Of the Dispersion Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism behind the DF microseism energy is attributed to "the interaction of opposing wave fields having nearly the same wave number, generating a pressure excitation pulse nearly unattenuated to the ocean floor" (Bromirski et al, 2005). For this reason, most of the research on DF microseisms is based on data collected on coastal seafloors or coastal land (Babcock et al, 1994;Webb, 1998;Brooks et al, 2009;Stephen et al, 2003;Sun et al, 2013). In terms of the generation mechanism and frequency range, two classes of DF microseism were recognized: (1) long-period DF (LPDF) microseism (f 0:085-0:2 Hz), which is generated by swells from distant storms, and (2) short-period DF (SPDF) microseism (f 0:2-0:5 Hz), which is excited by local storms (Dorman et al, 1993;Webb, 1998;Stephen et al, 2003;Bromirski et al, 2005).…”
Section: Introductionmentioning
confidence: 98%